The Relationship Between Quality Of Life And Sustainable Human Development - Benyahia ,Abdelhak; Rouaba, Mohammed (جامعة الوادي University of Eloued, 2025)
This study tries to prove whether there is a relationship between quality of life and sustainable human development in Algeria for the period 2016-2023 or not. It found that there is a relationship between them theoretically, which was not validated by the analytical aspect, and was validated by the linear trends of both variables, but proved that the linearity of sustainable human development is higher than the linearity of quality of life, which is the desired result in the reality of their relationship, as quality of life is intended to raise the efficiency and development of the human element, although the results of the linearity of both variables are statistically unacceptable, and finally result of the spread of data and correlation metrics confirmed that there is no relationship between QoL and SHD, whether linear or nonlinear.
مقال
Keywords: Quality of Life; Sustainable Human Development; Index; Relationship; Linear; Nonlinear; Correlation